Sovereignty as responsibility and the foundations of the new humanitarian interventionism - Piedrahita Ramírez, Luis Felipe (Estudios de Filosofía, 2015)
This article discusses the relationship posed by the Responsibility to Protect (R2P) around the dilemmas of sovereignty, intervention, security and human rights. The article deals with a reconstruction of the genesis of the new concept of sovereignty as responsibility (1) and human security approach (2) underlying the initial formulation of R2P, thereby contextualizing the contribution of the ICISS report to the creation of the new norm or doctrine (3). Finally, the paper reviews how the traditional doctrine of just war is reformulated and updated in the R2P (4).